Vigabatrin-Induced Visual Field Defects - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1998)
A drug surveillance database at Hoechst Marion Roussel, manufacturers of vigabatrin, identified 92 cases of symptomatic visual field defects associated with vigabatrin (usually as add-on therapy) between 1990 and 1997.